Pediatric tuberculosis under six years old: an 18-year experience of a level II hospital - Vieira, Joana Gomes; Ribeiro, Andreia Fiúza; Correia, Paula; Loureiro, Helena (International Journal Of Community Medicine And Public Health, 2023)
Background: Tuberculosis disease under six years is an indicator of recent transmission within the community. We aim to characterize tuberculosis disease in children under six years in a pediatric department of a level II hospital in the Lisbon metropolitan area, which serves a high percentage of immigrants from Portuguese-speaking African countries. Methods: Retrospective and descriptive study of tuberculosis disease cases treated in our Department between January 2004 and December 2021 (18 years). Descriptive analysis of the collected data was performed using SPSS Statistics® 25. Results: 25 patients were included, 60% diagnosed between 2016 and 2021. Five patients were born in countries with high TB incidence and 11 other patients had immigrant families from such countries. Ten out of 13 patients not immunized with BCG had the recommendation to do so. A close contact with tuberculosis was known in 15 patients, and in seven of those the system for TB prevention failed. At diagnosis: 4/25 patients had disseminated tuberculosis (three miliary and one congenital). Conclusions: The increase in tuberculosis disease cases under six years in the last three years points to some pitfalls in tuberculosis surveillance and transmission prevention. New studies and institutional protocols are needed to improve the effectiveness of the network involved in TB prevention and treatment.